Análisis y Evaluación de la calidad del agua en la cuenca del Río Teusacá municipio de Sopó (2022)
Water is a vital compound for our life and that of ecosystems; over the years, this is being affected due to the activities that human beings have been implementing. The use of the water resource is essential, so it is vital to study the quality of the water and the permissible ranges, according to the utility that is going to be given to it. This research is carried out in a timely manner in the lower basin of the Teusacá River, jurisdiction of the municipality of Sopo, for this work geographic information systems techniques were used and the monitoring of different parameters of water quality such as: pH, conductivity electricity, temperature and dissolved oxygen, this in order to relate the quality of the river water with the different social, cultural and economic activities of the municipality